Implementation of a Generalized Predictive Controller with Fuzzy Suppression and Weighting Parameters for a Level Plant with Interconnected Concentric Tanks - Correa Tamayo, Sara; Ospina Correa, Juan David; Ramírez Urrego, Jhon Alexander; Lopez Lezama, Jesus Maria; Muñoz Galeano, Nicolas (Ingeniería, 2025)
Context: This paper employs fuzzy logic in the unconventional adjustment of suppression and weighting factors within a generalized predictive controller (GPC). Method: The control strategy is applied to a level plant featuring interconnected concentric tanks. For the tuning process, a fuzzy proportional-integral-derivative PID controller is compared against the proposed GPC equipped with fuzzy suppression and weighting parameters. Evaluation metrics related with response time and integration criteria are employed in this comparison Results: The results demonstrate the superiority of the GPC combined with fuzzy logic over the fuzzy PID controller. Dynamic weighting factors contribute to enhanced control performance, as evidenced by the evaluation metrics. Conclusions: The proposed approach proved to be effective in improving control performance in the tested system. This approach offers a promising alternative to traditional methods, especially in systems where dynamic adjustments are beneficial.